LCS-1 inhibition of superoxide dismutase 1 induces ROS-dependent death of glioma cells and degradates PARP and BRCA1 - Ling, Min; Liu, Qing; Wang, Yufei; Liu, Xueting; Jiang, Manli; Hu, Jinyue (Frontiers in Oncology, 2022)
Gliomas are characterized by high morbidity and mortality, and have only slightly increased survival with recent considerable improvements for treatment. An innovative therapeutic strategy had been developed via inducing ROS-dependent cell death by targeting antioxidant proteins. In this study, we found that glioma tissues expressed high levels of superoxide dismutase 1 (SOD1). The expression of SOD1 was upregulated in glioma grade III and V tissues compared with that in normal brain tissues or glioma grade I tissues. U251 and U87 glioma cells expressed high levels of SOD1, low levels of SOD2 and very low levels of SOD3. LCS-1, an inhibitor of SOD1, increased the expression SOD1 at both mRNA and protein levels slightly but significantly. As expected, LCS-1 caused ROS production in a dose- and time-dependent manner. SOD1 inhibition also induced the gene expression of HO-1, GCLC, GCLM and NQO1 which are targeting genes of nuclear factor erythroid 2-related factor 2, suggesting the activation of ROS signal pathway. Importantly, LCS-1 induced death of U251 and U87 cells dose- and time-dependently. The cell death was reversed by the pretreatment of cells with ROS scavenges NAC or GSH. Furthermore, LCS-1 decreased the growth of xenograft tumors formed by U87 glioma cells in nude mice. Mechanistically, the inhibition of P53, caspases did not reversed LCS-1-induced cell death, indicating the failure of these molecules involving in cell death. Moreover, we found that LCS-1 treatment induced the degradation of both PARP and BRCA1 simultaneously, suggesting that LCS-1-induced cell death may be associated with the failure of DNA damage repair. Taking together, these results suggested that the degradation of both PARP and BRCA1 may contribute to cell death induced by SOD1 inhibition, and SOD1 may be a target for glioma therapy.